Hydrogel Microlasers for Versatile Biomolecular Analysis Based on a Lasing Microarray. Issue 1 (6th September 2020) - Gong, Xuerui; Qiao, Zhen; Guan, Peng; Feng, Shilun; Yuan, Zhiyi; Huang, Changjin; Chang, Guo-En; Chen, Yu-Cheng
Abstract : Biological microlasers, which utilize lasing emission as a sensing signal, have recently emerged as a promising approach in biotechnology. As such, biolasers with functionality are of great significance for the detection of tiny molecular interactions in biological systems. Despite the considerable progress achieved in biomaterial‐based microlasers, the ability to manipulate nanoscale biostructures and functionalize molecules in microcavity represents a grand challenge. Herein, the development of hydrogel microlasers by exploiting the versatility and controllability of hydrogels is reported, where whispering‐gallery‐mode lasing is achieved by printing hydrogel droplets on a mirror. Lasing behaviors and fundamental characteristics of hydrogel lasers are explored under various water‐monomer ratios and crosslinking degrees. Furthermore, a hydrogel lasing microarray is developed, providing a novel approach to study molecular interactions within the 3D hydrogel network structure. To demonstrate the potential application and functionality, Forster resonance energy transfer (FRET) peptide lasing is exploited for molecular analysis. Single‐mode FRET laser emission is achieved by tuning the Forster distance in hydrogel droplets. Finally, different types of biomolecules are encapsulated to form biolasing. These findings not only highlight the ability of hydrogel biolasers for high‐throughput biomolecular analysis but also provide deep insights into the relationship between biostructure and laser physics. Abstract : Herein, the development of a hydrogel biological microlaser by exploiting the high versatility of hydrogels is reported, demonstrating the ability to manipulate nanoscale biostructures and functionalize molecules in a microcavity. The concept of a lasing microarray is devised through inkjet printing, paving new avenues for studying biomolecular interactions in a wide range of biomedical applications.